Comparison of Tooth Root Bending Fatigue Life Between 18CrNiMo7-6 and 20CrMnTi Materials - Daojun Li; Qingbo Lu; Deping Liu (Jixie chuandong)
In order to compare the tooth root bending fatigue life of 18CrNiMo7-6 and 20CrMnTi gears，based on the fatigue characteristics of these two materials，the gear model is built by using the GearTrax plug-in in the 3D modeling software SolidWorks. Through the finite element analysis software Workbench， the statics analysis of the single tooth of the gear is performed，and then the static analysis result is introduced into the fatigue analysis software FE-SAFE，in combination with the load spectrum information， the fatigue life of the two gears are calculated，and the obtaining life cloud maps are analyzed and compared. The feasibility of the simulation method is verified by experiments. The results show that， under the same load conditions， the fatigue life of gears with 18CrNiMo7-6 is slightly greater than that with 20CrMnTi， it is close to the experimental results. The analysis results have a certain guiding role for engineering practice.